Local Community Perspectives on Naming the Mbombo Aukhu Tourism Destination in Oladano Village, Nias - Afore Tahir Harefa; Benifaeri Telaumbanua; Asirida Waruwu (Tinta Emas Institute, 2024)
Each tourism destination has unique characteristics that attract tourists' attention and interest. This research focuses on the naming of the Mbombo Aukhu tourism destination in Oladano village, Idanogawo-Nias subdistrict. The objective is to understand the local community's perspective on the naming of Mbombo Aukhu as a tourism destination. Using qualitative research methods, data were collected through observation and direct interviews with local community members. The findings reveal that the name Mbombo Aukhu originates from the naturally warm spring water in the area, which is believed to contain sulfur. The name